Nutritional Services in Hills of Uttarakhand- An Overview - Pratiti Haldar; Lekha Viswanath; Ashok Kumar Srivastava (Medsci Publications, 2023)
A healthy individual makes up a healthy community, a healthy state and a healthy country. As the saying goes - "Health is Wealth". So, health is something which cannot be ignored. In order to maintain health, one needs to take into consideration the nutritional needs of the body and this is of utmost importance especially during the early phase of growth periods in children. Our country is facing problem of malnutrition in children which is of alarming concern and inspite of numerous projects planned by the government of our country still the bane of malnutrition prevails. There needs to be an additional intervention planned at grassroot level keeping in consideration every geographical terrain, cultural and ethnic practices in related to feeding and rearing. This will not only help in combatting the problem of malnutrition but will also keep the mother and family of child aware of nutrition status of their children. The need to strengthening our policies and services at grassroot level is of prime concern as a lot policies and services are only limited to the documents.